Beliefs about tuberculosis in Bay, Laguna and their implications to health education - Bailon, Salvacion Guysayko 1943- (1975)
This study determined the beliefs about tuberculosis among the people of Bay, Laguna, pilot town and seat of the University of the Philippines Comprehensive Community Health Program, and their implications to health education.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Tuberculosis -- Public opinion. -- Bay, Laguna; Health education -- Bay, Laguna